(untitled) (Publicaciones en Ciencias y Tecnología, 2022)
A super pressurized balloon is a sealed structure made of a thin linear low density polyethylene (LLDPE) membrane reinforced with cords, with tension calculated to counterbalance intense stresses on the film as shown in this paper. We propose a double super pressurized (DSP) balloon design, with an inner membrane inside a slightly larger one. Both membranes are connected by LLPDE films joining the cords of each balloon, creating gore-panels surrounding the internal membrane. The internal globe is filled with Hydrogen, that is inexpensive but inflammable while the external gores will be filled with nonflammable gas Helium, but very expensive. As volume of the internal globe is much larger than the volume of the exterior panels, the cost of filling this double balloon is drastically reduced, compared with traditional balloons completely filled with Helium. In the DSP balloon Hydrogen must go first through the exterior panels in order to escape, then the loss rate of Hydrogen is largely reduced, increasing the security in the use of Hydrogen filled balloons. Also, the double balloon can resist the breaking of the exterior membrane, even the rupture of the inner membrane provided they do not break in the same section.